2016
DOI: 10.1002/lsm.22518
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the treatment of melasma lesions exhibiting increased vascularity with the 595‐nm pulsed dye laser combined with the 1927‐nm fractional low‐powered diode laser

Abstract: Melasma lesions exhibiting subtle or sub-clinical telangiectatic erythema may be improved by combined vascular-targeted laser therapy together with fractional low-powered diode laser therapy. A parallel improvement in telangiectatic erythema suggests a relationship between the underlying vasculature and hyperpigmentation. There is a low risk of adverse effects and overall patient satisfaction is high. Follow-up to optimize treatment parameters and determine long-term durability is needed. Lasers Surg. Med. 49:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…24,27 Moreover, long-term remission is particularity difficult in patients with melasma due to the potential side effects of long-pulsed or QSNL systems. 19,27,28 Recent studies, therefore, have focused on treatments using laser systems that target cutaneous vasculature 29,30 or energy-based devices 9,31 to increase the success rate and rate of clinical improvements.…”
Section: Discussionmentioning
confidence: 99%
“…24,27 Moreover, long-term remission is particularity difficult in patients with melasma due to the potential side effects of long-pulsed or QSNL systems. 19,27,28 Recent studies, therefore, have focused on treatments using laser systems that target cutaneous vasculature 29,30 or energy-based devices 9,31 to increase the success rate and rate of clinical improvements.…”
Section: Discussionmentioning
confidence: 99%
“…As a hypothesis, rather than considering the thermal relaxation time or stress relaxation time of the vasculature, we might additionally suggest that it is the picosecond domain‐related photomechanical effect on the endothelium of the target vessels, coupled with the selective absorption of the 595 nm energy in the erythrocytes, which could be affecting the overproduction of endothelial adhesion molecules from the hyperactive microvasculature. This could in turn influence the intracellular adhesion molecule signaling from the fibroblasts to the keratinocytes, thus breaking the inflammatory cycle and reducing the melanin‐stimulating hormone effect on the lesional melanocytes . This is an attractive hypothesis, but requires further immunohistochemical study to establish proof.…”
Section: Discussionmentioning
confidence: 99%
“…However, some PIH was reported along with relatively frequent relapses. Interestingly, a recent retrospective study that used thulium laser and PDL showed an improvement superior to 50% in six of the 11 patients without any PIH or rebound . Prospective randomized comparative trials are still required to determine the usefulness of this device for treating melasma.…”
Section: Clinical Indicationsmentioning
confidence: 99%
“…Interestingly, a recent retrospective study that used thulium laser and PDL showed an improvement superior to 50% in six of the 11 patients without any PIH or rebound. 161 Prospective randomized comparative trials are still required to determine the usefulness of this device for treating melasma. Ablative fractional lasers can also be used for enhancing the penetration and efficacy of HQ.…”
Section: Recommendationmentioning
confidence: 99%